Rhodium-catalyzed 1,4-addition of triorgano(vinyl)silanes to electron-deficient olefins and application towards the preparation of functionalized organoboron compounds - Ng, Yu Rui (2010)
It was recently discovered in the author’s group that the transmetalation of typically unreactive triorgano(vinyl)silanes could be accomplished with [RhCl(CO)2]2, leading to the development of a rhodium-catalyzed acylation of triorgano(vinyl)silanes with acid anhydrides. Employing a similar transmetalat ion, a catalytic 1,4-addition of triorgano(vinyl)silanes with various electron deficient olefins was developed by the use of [RhCl(CO)2]2. This is the first example of the 1,4-addition of tetraorganosilicon compounds in the absence of any activating functional groups. This reaction was found to be tolerant towards vinylsilanes with different substitution patterns. In order to investigate the reactivities of the carbon-boron and carbon-silicon bonds towards [RhCl(CO)2]2, alkenyl compounds having both organometallic bonds were applied in [RhCl(CO)2]2 catalyzed acylation and 1,4-addition reactions. It was found that the carbon-silicon bond could be selectively cleaved, thereby retaining only the boranyl group. This led to the synthesis of acylated and alkylated organoboron compounds, which were previously difficult to synthesize.